Avaliação da função sexual da mulher no período gestacional - Pereira, Marina Cortez (2015)
The human sexual response is influenced by several biological, psychological, socioeconomic, cultural, religious, historic, among other, factors. It is known that during pregnancy woman's body goes through many changes, which can influence in their sexual function. Sexual changes in women may occur at various stages of the sexual response cycle, whether in desire, arousal, lubrication, or orgasm, which occurrence is peculiar during pregnancy. The present study aimed to evaluate the sexual function of women during pregnancy. The methodology used was quantitative, descriptive, cross-sectional and analytical approach. The sample consisted of 161 pregnant women at low risk who were treated at health units in the network of Primary Health in Alfenas-MG. Data were collected between October 2013 and January 2014, and two instruments were used: the first one for the characterization of participants composed by sociodemographic variables, obstetric and medical history related to sexual function, elaborated by the author; and the Sexual Quotient - Female Version to measure performance and sexual satisfaction of respondents. This investigation was approved by the Ethics Committee on Human Research of the Federal University of Alfenas. After collecting and tabulating the data, it was used the Statistical Package for Social Sciences software version 17.0 for descriptive analysis and statistical tests such as Shapiro-Wilk normality test, Mann-Whitney, Kruskal Wallis test, Student-Newman-Keuls and Spearman correlation coefficient. As a result, it was found that most of the women were between 18-30 years old, single, brown, Catholic, had concluded high school, and had laboral activity, with incomes between one and two minimum wages, and have no children. The frequency of sexual intercourse was between once to twice a week and the majority considered to have a good, very good and great / excellent sexual partner relationship. Regarding the correlations and associations between the QS-F and sociodemographic factors, obstetric history and sexual functions, variables: family income, education level, frequency of weekly sexual intercourse and consideration against the sexual relationship with the partner, showed significant statistics. Regarding the evaluation of the QS-F, pregnant women showed satisfactory performance concerning sexual activity with results from "good to excellent" and "fair to good". Given the results, it is necessary that the health professionals act in line with actions and interventions aimed at prevention, rehabilitation and the promotion of sexual health in the context of pregnancy. The nurse, for being part of the daily care, should establish effective communication about sexuality with its users during the offered service.